DESIGN, IN VITRO, AND EX VIVO EVALUATION OF BUDESONIDE BUCCAL PATCH USING XANTHAN GUM AS A NATURAL POLYMER MATRIX - PREETHI GB; SUBHAM ROY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The present study aimed to formulate sustained-release mucoadhesive buccal patches of bio-pharmaceutical classification class II drug budesonide (BUD) using the mucoadhesive polymer xanthan gum (XG) and the film-forming agent hydroxypropyl methylcellulose (HPMC) E-15. Methods: To enhance the solubility of BUD, a solid dispersion of BUD (B-SD) was prepared using Soluplus as a solubilizing agent through the solvent evaporation method. Buccal patches of B-SD (BU1–BU9) were formulated using the solvent casting technique. The patches were evaluated for drug content, weight variation, thickness, folding endurance, moisture content, mucoadhesive strength, swelling index, and in vitro drug release. Results: The formulations exhibited statistically significant differences in physical properties (p<0.05). Formulation BU9, containing higher polymer concentrations, showed significantly greater swelling index, mucoadhesive strength, and sustained in vitro drug release (96.41±0.003%) compared to the pure drug patch (PDP) (40.13±0.015%, p<0.0001). Drug release followed a non-Fickian Super Case II transport mechanism. Ex vivo permeation studies of BU9 demonstrated a cumulative permeation of 4.26±0.042 mg/cm2 with a flux of 0.133 mg/cm2/h, both significantly higher than the PDP (p<0.05). The optimized BU9 patch was further characterized by FT-IR, differential scanning calorimetry, and X-ray diffraction, confirming the absence of drug-excipient interactions. Conclusion: Buccal patches of BUD can be successfully formulated using XG in combination with HPMC E-15 to achieve sustained drug release with enhanced mucoadhesive and permeation properties.